UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL 96% BUNGA KECOMBRANG DALAM BENTUK FORMULASI DAN SEDIAAN MASKER GEL - Arti Wahyu Utami; Rifkarosita Putri Ginaris; Tri Yudianto; Na’imatul Retno Faizah; Dyah Rohma Wati (Sekolah Tinggi Ilmu Kesehatan Tujuh Belas, Karanganyar, JAwa, Indonesia, 2021)
A health problem that occurs during adolescence, puberty and sensitive facial skin is acne. Acne that arises apart from being supported by hormonal factors, on the other hand, can also be caused by the uncontrolled activity of normal flora, causing a decrease in self-confidence in socializing with the environment. Bacteria that initially become normal flora on facial skin then grow because they are uncontrolled and a person's level of cleanliness decreases, ideally in the form of Staphylococcus aureus (SA) and Propinobacterium acnes (PS). Efforts to prevent the growth of bacteria that cause acne, apart from consuming nutritious food, also recommend using cosmetics made from natural ingredients and have antibacterial properties. One of the cosmetics used to maintain cleanliness and prevent the growth of acne-causing bacteria is a gel mask. The advantage of the gel mask preparation is that it does not cause heat, feels cool, and is able to remove dirt from facial skin optimally. The gel mask preparation used in this research was 96% ethanol extract of the kecombrang flower plant. Combrang flowers have been proven to contain phytochemicals which are effective as a source of antibacterial properties. This research aims to provide the latest scientific information on each formulation and gel mask preparation made from the active ingredient 96% ethanol extract of kecombrang flowers in inhibiting the growth of the two test bacteria, namely SA and PS. This research is an experimental laboratory by making a formulation and preparation of a gel mask using the active ingredient 96% ethanol extract of the kecombrang flower plant at a concentration of 5%; 10% ; and 15%. The results of this research have proven that each gel mask preparation correlates positively as an antibacterial for SA and PS. The conclusion in this study is that a concentration of 15% is the optimal concentration as an antibacterial for SA and PS